Investigation on the Photoelectrocatalytic Activity of Well-Aligned TiO2 Nanotube Arrays - Xiaomeng Wu; Zhaohui Huang; Yangai Liu; Minghao Fang (International Journal of Photoenergy)
Well-aligned TiO2 nanotube arrays were fabricated by anodizing Ti foil in viscous F− containing organic electrolytes, and the crystal structure and morphology of the TiO2 nanotube array were characterized and analyzed by XRD, SEM, and TEM, respectively. The photocatalytic activity of the TiO2 nanotube arrays was evaluated in the photocatalytic (PC) and photoelectrocatalytic (PEC) degradation of methylene blue (MB) dye in different supporting solutions. The excellent performance of ca. 97% for color removal was reached after 90 min in the PEC process compared to that of PC process which indicates that a certain external potential bias favors the promotion of the electrode reaction rate on TiO2 nanotube array when it is under illumination. In addition, it is found that PEC process conducted in supporting solutions with low pH and containing Cl− is also beneficial to accelerate the degradation rate of MB.